HUBUNGAN PENGETAHUAN DAN PERSEPSI PRIA DENGAN PEMAKAIAN KONDOM DI WILAYAH KERJA PUSKESMAS RIMBO DATA - Suryanti .; Acholder Tahi Perdoman (Universitas Batam, 2019)
A condom is a sheath made of latex which is caused by an erect penis or vagina that acts as a protector to prevent semen or fluid from ejaculating when the penis is in the vagina. Men's participation in joining the Family Planning program is quite low. This has also reduced men's participation in using condom contraception. The purpose of this study was to determine the Relationship between Knowledge and Perceptions of Men with Condom Use in the work area of the Rimbo Data Center. This research is quantitative research with analytic descriptive design and cross-sectional approach conducted in January 2019. The sampling technique is purposive sampling with a sample size of 80 people. Data were analyzed univariately and bivariate by computer using the chi-square statistical test. The results obtained from 80 samples, based on this univariate analysis (46.2%) had a low level of knowledge, (53.8%) had a negative perception, and most (63.8%) respondents did not use contraceptives condom. Based on bivariate analysis states there is a significant relationship between male knowledge with the use of condoms with a value of p-value = 0,000 <0.05. The perception of men with the use of condoms states that there is a significant relationship between perception with the use of condoms with the results of p-value = 0,000 <0.05. It is expected that the results of this study can increase the knowledge and perception of the community through counseling, especially regarding condom contraception. Based on the results of this study it can be concluded that there is a relationship between Knowledge and Perceptions of Men with Condom Use in the work area of Rimbo Data Center.